The Emergency Management Strategies for Catastrophic Diseases: A Multidisciplinary Approach in Healthcare Facilities: Emergency Management Strategies for Catastrophic Diseases: A Multidisciplinary Approach in Healthcare Facilities - Sitepu, Rahmadani (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Background: Catastrophic diseases, such as stroke, acute myocardial infarction, and respiratory failure, are medical conditions with high mortality and morbidity. Fast and appropriate treatment in emergency situations is crucial to the patient's prognosis. A multidisciplinary approach in healthcare facilities is a key strategy in improving the quality of care and patient safety. Objective: This study aims to explore emergency management strategies in catastrophic diseases with a multidisciplinary approach in health facilities and analyze their effectiveness based on univariate and bivariate data. Methods: This study used a quantitative method with a cross-sectional design in several referral health facilities. Data is collected through patient medical records, direct observation, and interviews with medical personnel. The analysis was carried out with descriptive statistics (univariate) to describe patient characteristics and medical procedures, and chi-square and logistic regression (bivariate) tests to test the association between multidisciplinary involvement and patient clinical outcomes. Conclusion: Emergency management strategies based on a multidisciplinary approach have been proven to improve the effectiveness of handling catastrophic diseases in healthcare facilities. The involvement of various medical professions can speed up decision-making and improve patient safety rates. Therefore, strengthening coordination between professions and increasing the capacity of health facilities are essential steps in mitigating the risk of catastrophic diseases.